ANALISIS KEMACETAN SIMPANG TAK BERSINYAL JALAN PADAT KARYA – JALAN SUMATERA KOTA PRABUMULIH MENGGUNAKAN PKJI 2023 - Sarwandy, M. Hijrah Agung; Royan, Noto; Asep, Muhammad (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2024)
There will undoubtedly be heavy traffic in this location, especially at the intersection of Jalan Padat Karya, as Prabumulih is one of the cross-Sumatra cities with heavy traffic. The second economic hub of Prabumulih City is the Karya Intensive Road. When primary data collecting takes place in the field, descriptive and quantitative research methodology is employed. 7 days a week, Monday through Sunday, from 07.00 to 18.00. Road width measurements are made on the spot at each approach using a measuring tool. Following the collection of all primary and secondary data, analysis will be conducted utilizing PTV Vissim Version Student for traffic modeling and the 2023 PKJI Book. Intersection performance analysis using PKJI 2023 produces results traffic flow is 836.2 pcu/hour, free flow speed is 43.70 km/hour, capacity of 1468 pcu/hour, degree of saturation of 0.85. Based on the results above, the service level flow section is D. The intersection model after being given a signal changes if using APILL with 2 phases because of the level of service that occurs changed to level A.